Forming limit diagram of an ultra-thin commercially pure titanium sheet: Combined experimental–numerical approach - Kyung Mun Min (Journal of Materials Research and Technology, 2025)
This study presents a methodology for determining the forming limit diagram (FLD) of an ultra-thin (0.1 mm) commercially pure titanium (CP–Ti) sheet developed for use in metallic bipolar plates for fuel cells. Due to its extreme thinness and pronounced planar anisotropy, the standard specimen geometries specified in ISO 12004-2 were found to be inadequate for FLD evaluation. To address this, optimized specimen geometries were designed using finite element (FE) simulations incorporating the anisotropic evolutionary Yld2000-2d yield function. Additional simulations using actual bipolar plate geometries revealed that major strain direction during forming may align with either the rolling or transverse direction. Based on these findings, a new evaluation method was proposed to derive direction-dependent FLDs, while maintaining full compliance with the ISO 12004-2 procedure. Experimental validation confirmed that the proposed methodology is suitable for assessing forming limits, revealing a strong dependence of FLD shape on the major strain direction. This work offers a practical and accurate approach for evaluating directional formability in ultra-thin CP-Ti sheets, providing valuable insight into their deformation behavior driven by hexagonal close-packed (HCP) crystal structure and strong crystallographic texture.